Relevansi DSN-MUI Dengan Pelaku BSI Dalam Akad Murabahah Di Sumatera - Dame Siregar; Fauzi Rizal; Sawaluddin Siregar; Neila Hifzhi Siregar (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Murabahah is a form of sale and purchase contract that is based on rules set by syara'. Murabahah is the most dominant contract transaction used by Islamic banks in Indonesia. In carrying out murabaha transactions, Islamic banks must follow the rules set out in Islamic law and must also comply with the rules issued by the DSN-MUI. With the implementation of compliance with these rules, murabaha contracts carried out by Islamic banks will avoid elements of usury. One of the best achievements made by an Islamic financial institution is avoiding the element of usury, because basically Islamic banks are bound by Islamic rules. Keywords: Murabahah, DSN-MUI, Bank Syariah Indonesia